2020
DOI: 10.1002/per.2262
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationships between Mobility Behaviours and Indicators of Subjective Well–Being Using Smartphone–Based Experience Sampling and GPS Tracking

Abstract: People interact with their physical environments every day by visiting different places and moving between them. Such mobility behaviours likely influence and are influenced by people's subjective well‐being. However, past research examining the links between mobility behaviours and well‐being has been inconclusive. Here, we provide a comprehensive investigation of these relationships by examining individual differences in two types of mobility behaviours (movement patterns and places visited) and their relati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 84 publications
0
47
0
Order By: Relevance
“…As Matz et al [6] define it, psychological profiling is "the automated assessment of psychological traits from digital footprints". Over the past decade, researchers have been tapping into a broad variety of data sources for psychological profiling, including social media data (e.g., Facebook likes and status updates [2,7]), mobile sensing data [8], music listening preferences [9,10], mobility behaviors [11] as well as financial transaction records [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…As Matz et al [6] define it, psychological profiling is "the automated assessment of psychological traits from digital footprints". Over the past decade, researchers have been tapping into a broad variety of data sources for psychological profiling, including social media data (e.g., Facebook likes and status updates [2,7]), mobile sensing data [8], music listening preferences [9,10], mobility behaviors [11] as well as financial transaction records [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These behavioral tendencies, in turn, may influence variables of interest to psychologists and other social scientists (e.g., mental health). For example, past work has found that distance travelled is related to anxiety, affect, and stress (Müller, Peters, Matz, Wang, & Harari, 2020).…”
Section: Interpreting Mobility Patternsmentioning
confidence: 99%
“…Sensing tools provide opportunities to capture accurate log data of phone use (Stachl et al, 2020) and notifications (Mehrotra et al, 2017). In addition, smartphone sensing provides rich information (e.g., GPS, acceleration) to ascertain mobility features (e.g., places visited, transportation modes) (Müller, Peters, Matz, Wang, & Harari, 2020). In these ways, novel mobile methods can provide deeper insights into the psychological terrain of mobile technology and daily mobility, especially when used in tandem with one another and infused with theoretical rigor.…”
Section: The Psychology Of Mobile Technology and Daily Mobilitymentioning
confidence: 99%
“…Furthermore, extraverts tend to visit more places and travel farther than introverts (Alessandretti et al, 2018). Mobility patterns also correspond with mental health profiles (see Müller et al, 2020). For example, a wide variety of mobility features (e.g., lower regularity of movement) have been used to predict depression with relatively high levels of accuracy (Canzian & Musolesi, 2015;Saeb, Lattie, Schueller, Kording, & Mohr, 2016).…”
Section: Why Mobility Matters To the User-device Connectionmentioning
confidence: 99%